New explosive materials through covalent and non-covalent synthesis: Investigation of explosive properties of trinitrotoluene: Acridine and picric acid: Acridine - Şen, Nilgün; Pons, Jean-François; Kurtay, Gülbin; Yüksel, Bayram; Nazir, Hasan; Khumsri, Akachai; Atakol, Orhan (Elsevier, 2023)
Trinitrotoluene (TNT) and picric acid (PIC) suffer from suboptimal thermal and impact sensitivities, which severely hinder their real-world use. We here demonstrate how co-crystallization with acridine (ACR) can improve these properties of TNT and PIC without detrimentally affecting their explosive performance. Remarkably, while PIC:ACR formed readily, attempts to co-crystallise TNT with ACR led to formation of new covalent bonds between the co-formers, thereby creating a new molecular entity. The structure and energetic behaviour of both novel solid forms (PIC:ACR and TNT-ACR) were characterised using a range of experimental and computational tools, indicating that both materials have improved thermal and mechanical stability but explosive performance has decreased to some extent. These findings will increase the likelihood of rational energetic material design in the future and open a new chapter in this discipline.
Keywords: Energetic salts; Picric acid; TrinitrotolueneAcridine; Non-covalent interactions; Carbanion adducts